N-Methoxy-1,3-oxazinane nucleic acids (MOANAs) - a configurationally flexible backbone modification allows post-synthetic incorporation of base moieties - Afari Mark N. K.; Virta Pasi; Lönnberg Tuomas (ROYAL SOC CHEMISTRY, 2022)
(2R,3S)-4-(Methoxyamino)butane-1,2,3-triol was converted into a protected phosphoramidite building block and incorporated into the middle of a short DNA oligonucleotide. O1 and O3 of the (2R,3S)-4-(methoxyamino)butane-1,2,3-triol were engaged in phosphodiester linkages, leaving O2 and the methoxyamino function available to form an N-methoxy-1,3-oxazinane ring through reaction with an aldehyde. In modified oligonucleotides thus obtained, the oxazinane ring formally replaces the furanose ring and the aldehyde, the base moiety of natural nucleosides. The feasibility of synthesizing base-modified oligonucleotides by this approach was demonstrated with several aromatic and aliphatic aldehydes featuring various functional groups.